Authorship Indicators in Perfect Score Essays on the Enem: a Resonance of Enunciative Voices - Trindade, Marcela Ribeiro; Fonseca, Anna Clara Souza; Silva, Anny Karoline Santana; Maia, Maria Cristina Ruas de Abreu (Revista Letras Raras, 2024)
This work aims to analyze the management of enunciative voices in two perfect score essays from the Enem 2021, where the writers employed the strategy of including other voices to meet competencies two and three, derived from a set of five mandatory competencies, as outlined in the Participant's Guide of the Enem (2020). Specifically, it seeks to describe whether the presence of these voices contributes to the erasure of the writer or reveals signs of authorship in the selected samples. Theoretically, the study draws from the framework of discursive studies, emphasizing the contributions of Bakhtin (1997, 2011) and Possenti (2002) on the notion of authorship, coupled with the studies of Bronckart (1999), Boch, and Grossmann (2002) on the manifestation of enunciative voices in texts. Methodologically, this research is characterized as qualitative and interpretative, applied to a corpus of two perfect score essays from Enem 2021, extracted from the G1 website. In that year, the theme proposed by the exam was "Invisibility and civil registration: guarantee of access to citizenship in Brazil," which required candidates to meet the five competencies of the Enem related to textual and linguistic knowledge and the use of a sociocultural repertoire adopted as an argument of authority to validate each writer's perspective. After the analyses, the results contradict the erasure of authorial voices, as the resonance of enunciative voices complies with competencies two and three and serves to validate the discourse defended by the writer, revealing indications of authorship.